Prostate cancer cell malignancy via modulation of HIF-1 alpha pathway with isoflurane and propofol alone and in combination - Huang,H; Benzonana,LL; Zhao,H; Watts,HR; Perry,NJS; Bevan,C; Brown,R; Ma,D (British Journal of Cancer, 2014)
Background: Surgery is considered to be the first line treatment for solid tumours. Recently, retrospective studies reported thatgeneral anaesthesia was associated with worse long-term cancer-free survival when compared with regional anaesthesia. This hasimportant clinical implications; however, the mechanisms underlying those observations remain unclear. We aim to investigate theeffect of anaesthetics isoflurane and propofol on prostate cancer malignancy.Methods: Prostate cancer (PC3) cell line was exposed to commonly used anaesthetic isoflurane and propofol. Malignant potentialwas assessed through evaluation of expression level of hypoxia-inducible factor-1a (HIF-1a) and its downstream effectors, cellproliferation and migration as well as development of chemoresistance.Results: We demonstrated that isoflurane, at a clinically relevant concentration induced upregulation of HIF-1a and itsdownstream effectors in PC3 cell line. Consequently, cancer cell characteristics associated with malignancy were enhanced, withan increase of proliferation and migration, as well as development of chemoresistance. Inhibition of HIF-1a neosynthesis throughupper pathway blocking by a PI-3K-Akt inhibitor or HIF-1a siRNA abolished isoflurane-induced effects. In contrast, the intravenousanaesthetic propofol inhibited HIF-1a activation induced by hypoxia or CoCl2. Propofol also prevented isoflurane-induced HIF-1aactivation, and partially reduced cancer cell malignant activities.Conclusions: Our findings suggest that modulation of HIF-1a activity by anaesthetics may affect cancer recurrence followingsurgery. If our data were to be extrapolated to the clinical setting, isoflurane but not propofol should be avoided for use in cancersurgery. Further work involving in vivo models and clinical trials is urgently needed to determine the optimal anaesthetic regimenfor cancer patients.